Thermal reduction of graphene oxide mixed with hard carbon and their high performance as lithium ion battery anode. (April 2016) - Zhang, Xiang; Han, Shaochang; Xiao, Pingan; Fan, Changling; Zhang, Weihua
Abstract: Graphene oxide in hard carbon/graphene composite is reduced by thermal treatment in inert atmosphere at a temperature in the range of 800–1100 °C. In this way, hard carbon/graphene composites with different effect of reduction on graphene oxide are obtained. Increasing heat treat temperature improves the reduction of graphene oxide (C/O atomic ratio in the range of 44–104) and diminishes the specific surface area and pore volume slightly. Furthermore, these materials behave as high-performance lithium ion battery electrodes and exhibit large reversible capacity (in the range of 300–480 mAh g −1 ) at current density of 20 mA g −1, and superb stability over long-term cycling (78–82% of initial specific capacity after 500 cycles). Superior results are obtained with the electrode fabricated from the material treated at 1000 °C, which delivers 480 mAh g −1 and 170 mAh g −1 at current density of 20 and 2000 mA g −1, respectively. In addition, interesting results are obtained that electrodes prepared by two types of copper foils display a significant difference on galvanostatic charge/discharge capacity.